Objek Kajian Islam (Akidah, Syariah, Akhlaq) - Yazidul Bushtomi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The objects of Islamic study are: 1. Akidah, based on the Big Indonesian Dictionary, creed is a basic belief, a basic belief. The word aqidah, when viewed from Arabic, comes from the word "'Aqada-ya'qidu-'aqdan-'aqidatan" which means bond and agreement. While Akidah according to the term something that becomes a belief or truth in the human heart in accordance with Islamic teachings by sticking to the Qur'an and hadith. Akidah can also be interpreted as a form of belief or someone's belief. 2. Sharia, sharia in the context of the study of Islamic law more describes a collection of legal norms that are the result of the tasyri process. Tasyri 'is creating and implementing sharia. In the study of Islamic law, tasyri' is often defined as the determination of legal norms to organize human life, both in relation to God and with other human beings. 3. Morals, thermologically, morality means the behavior of a person who is driven by a conscious desire to do a good deed. Three experts in the field of morals, namely Ibn Miskawih, Muhammad al-Ghazali, and Ahmad Amin stated that morality is a character inherent in a person who can bring up good deeds without considering the mind first.